Python in Containers - Celmer, Kris (Packt Publishing, 2020)
All about containers, Docker, and Kubernetes for Python engineers. About This Video Become well-versed with using Docker tools to create top-class containers running your Python code Master Docker runtime tools such as Compose and Swarm Design your applications to run on Kubernetes and master writing Kubernetes object declarations In Detail Docker and Kubernetes are must-have skills for Python engineers these days. Whether your focus is on machine learning and data science or you use Python as a general programming language, you must understand Docker and Kubernetes, as they form the basis of modern cloud-native applications built using microservice architectures. In this course, you'll learn to do the following: Develop and explore machine learning, data science, and Jupyter Notebooks in Docker Run machine learning models in production with Kubernetes and Docker Swarm Package your Python code into containers Publish your containers in image registries Deploy containers to production, both in Docker and Kubernetes Build highly modular, container-based services in a microservices way Monitor and maintain containerized apps You can use the course in two ways: If you use Python for machine learning and data science, go top-down - start with section 7 to quickly develop practical Docker skills and use sections 2 to 6 to delve deeper into specific container topics If you want to use Python for building web apps and microservices, try the bottom-up approach - use the course in a linear way.
Online resource; Title from title screen (viewed March 24, 2020)
Keywords: Electronic videos